EP 35. Influence of gender on personality-brain structure relationships. Issue 9 (September 2016) - Nostro, A.; Müller, V.I.; Reid, A.T.; Eickhoff, S.B.
Abstract : Previous studies have shown that males and females differ in personality. In particular, gender differences have been reported for neuroticism and agreeableness (Costa et al., 2001 ), with women scoring higher on these two traits than men. Although gender has also been shown to influence brain structure, effects of gender on personality – brain relationships have hardly been investigated. Indeed, most studies treated gender as a covariate of no interest. (Hu et al., 2011 ). In this study, we used whole brain voxel-based morphometry (Ashburner and Friston, 2000 ) to investigate the influence of gender on associations between personality traits (assessed by the NEO FFI) and grey matter volume (GMV) in a large sample of 182 males and 182 females. Personality-GMV relationships were, on the one hand, assessed across the entire sample, and on the other hand, separately for males and females, with the aim of detecting associations both dependent on and independent of gender. Results revealed no significant correlations between any personality scale and GMV in the analyses across the entire sample. In contrast, when the sample was split by gender, significant positive associations between extraversion and GMV were observed in males, but not females, in precuneues/cuneus (Prc/Cun), left fusiform gyrus extending into cerebellum (lFFG/Cb), left thalamus and right cerebellum. Similarly, positive associations between conscientiousness and GMV were found only for males in lPrc/Cun. In addition, negative associations were found between neuroticism and GMV in cuneus/calcarine sulcus (Cun/CaS), lFFG/Cb and rFFG/Cb, again only in males. Interestingly, GMV in lPrc/Cun correlated with all three traits. Functional characterization (Laird et al., 2011 ) of this region revealed an association with perception of vision motion, explicit memory and action inhibition. Our finding suggests that men who tend to be more extroverted, conscientious, and emotionally stable, display higher GMV in lPrc/Cun, which might indicate that higher scores in those traits also go along with better abilities in these cognitive functions. In conclusion, our study demonstrated that neural correlates of personality are highly dependent on gender, which might be due to hormonal interplays or differences in brain organization between males and females. Furthermore, our results extend previous investigations, which focus on relationships between personality traits and performance in specific tasks, by providing possible neural substrates of those personality-behavior relationships.